Heterologous Expression of the Transcription Factor EsNAC1 in Arabidopsis Enhances Abiotic Stress Resistance and Retards Growth by Regulating the Expression of Different Target Genes - Liu, Can; Sun, Qinghua; Zhao, Lei; Li, Zhaoxia; Peng, Zhenghua; Zhang, Juren (Frontiers in Plant Science, 2018)
Heterologous expression of a transcription factor gene in a related species is a useful method for crop breeding and the identification of gene function. The differences in phenotype and target gene expression between HE lines (with the heterologous expression of an orthologue) and OX lines (with an overexpressed native gene) must be understood. EsNAC1, encoding a NAC protein and the orthologue of RD26 in Arabidopsis, was cloned from Eutrema salsugineum and introduced into Arabidopsis. The heterologous expression of EsNAC1 retarded the vegetative growth of Arabidopsis, and the transgenic plants (HE lines) showed much greater resistance to salt and oxidative stress than the wild type, Col-0. The HE lines accumulated 2.8-fold (8-hour light) of starch, 1.42-fold of Chlorophyll a and 1.31-fold of Chlorophyll b than Col-0 during the light period, with obvious differences compared to the RD26OX line. A genome-wide ChIP (chromatin immunoprecipitation analysis)-on-chip assay revealed that EsNAC1 targeted promoters of different genes compared to RD26. In HE lines, EsNAC1 could specifically up-regulate the expression level of transcription factor genes NAC DOMAIN CONTAINING PROTEIN 62 (ANAC062), INTEGRASE-TYPE DNA-BINDING PROTEIN (TINY2) and MYB HYPOCOTYL ELONGATION-RELATED (MYBH) to show more effective abiotic stress resistance than RD26OX lines. Moreover, DELTA1-PYRROLINE-5-CARBOXYLATE SYNTHASE 1 (P5CS1), TRYPTOPHAN BIOSYNTHESIS 2 (TRP2) or GALACTINOL SYNTHASE 2 (GOLS2), was also specifically regulated by EsNAC1 to retard the vegetative growth of HE lines, but not the brassinosteroid singling pathway in RD26OX lines. These differences in phenotypes and metabolism between the HE lines and the RD26OX line implied that the differential features could be produced from the diversity of target genes in the transgenic plants when the orthologue was introduced.